Odpowiedzi

2010-03-18T19:56:50+01:00
(x-3)(5-x)-2=(2-x)(x-4)+3
5x-x2-15-3x-2=2x-8-x2+4x+3
2x-x2-17=6x-x2-5 +x2
2x-17=6x-5 przenosimy x na jedną liczby na drugą
2x-6x=17-5
-4x=12
x=-3

(6-x)(2+x)+(3+x)(x-4)=2x+5
12+6x-2x-x2+3x-12+x2-4x=2x+5
12-12+6x-2x+3x-4x-x2+x2=2x+5
3x=2x+5
3x-2x=5
x=5

(x-5)(2+x)-(3-x)(2-x)=x-12
2x+x2-10-5x-6+3x+2x-x2=x-12
-10-6+2x-5x+3x+2x+x2-x2=x-12
-16+2x=x-12
2x-x=16-12
x=4

(2x-5)(x+1)-2=(1-x)(8-2x)+2x
2x2+2x-5x-5-2=8-2x-8x+2x2+2x
2x2-3x-7=2x2-8x+8 /2x2
-3x-7=-8x+8
-3x+8x=7+8
5x=15
x=3

2010-03-18T19:58:24+01:00
A)
(x-3)(5-x)-2=(2-x)(x-4)+3
(5x+3x)-2=(2x+4x)+3
8x-2=6x+3 /+2
8x=6x+5 /-6x
2x=5 /:2
x=2,5

b)
(6-x)(2+x)+(3+x)(x-4)=2x+5
(12-2x)+(3x-4x)=2x+5
36x+8x²=2x+5 /-2x
34x+8x²=5


c) (x-5)(2+x)-(3-x)(2-x)=x-12
(2x-5x)-(6+x²)=x-12
12x-5x³=x-12 /-x
11x-5x³=12


d)(2x-5)(x+1)-2=(1-x)(8-2x)+2x
(2x²-5)-2=(8+2x²)+2x /*1
2x²-5-2=8+2x²+2x /-2x²
-7=8+2x
2x+8=-7 /-8
2x=-15 /:2
x=7,5